Amorphous oxygen-rich molybdenum oxysulfide Decorated p-type silicon microwire Arrays for efficient photoelectrochemical water reduction. (September 2015) - Bao, Xiao-Qing; Petrovykh, Dmitri Y.; Alpuim, Pedro; Stroppa, Daniel G.; Guldris, Noelia; Fonseca, Helder; Costa, Margaret; Gaspar, Joao; Jin, Chuanhong; Liu, Lifeng
Abstract: We report the fabrication of p-type silicon (Si) photocathodes consisting of well-ordered Si microwire (Si-MW) arrays coupled with non-precious and earth-abundant amorphous oxygen-rich molybdenum oxysulfide (MoOx Sy ) as both a hydrogen evolution catalyst and a passivation layer. The MoOx Sy is conformally grown on the Si-MW surface through photo-assisted cyclic voltammetric (CV) deposition. By adjusting the cycle numbers of the CV deposition, Si-MW array electrodes with different MoOx Sy catalyst loadings (Si-MWs@MoOx Sy ) have been obtained and comprehensively characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Raman and Fourier-transform infrared spectroscopies. The photoelectrochemical performance of the Si-MWs@MoOx Sy cathodes toward water reduction is investigated and compared with that of platinum nanoparticle decorated Si-MW array electrodes (Si-MWs@PtNPs). An optimized Si-MWs@MoOx Sy photocathode is found to exhibit activity comparable to that of the Si-MWs@PtNPs one, with a much better stability in acidic medium. In neutral electrolyte, Si-MWs@MoOx Sy outperforms Si-MWs@PtNPs in terms of both activity and stability. Given the low materials cost, easy and well-established electrode fabrication procedure, and high demonstrated photoelectrochemical performance, the Si-MWs@MoOx Sy arrays reported here hold substantial promise for use as low-cost and efficient photocathodes for water reduction. Graphical abstract: p-type silicon microwire arrays coupled with a continuous and conformal MoOx Sy catalyst layer exhibit excellent photoelectrochemical performance towards water reduction. Highlights: Continuous, conformal, and thickness-tuneable coating of efficient, inexpensive, and durable oxygen-rich MoOx Sy HER catalyst on Si-MWs. Optimized Si-MWs@MoOx Sy electrodes exhibit water reduction activity close to that of Si-MWs@PtNPs, but showing much better stability. Optimized Si-MWs@MoOx Sy electrodes outperform Si-MWs@PtNPs in neutral electrolyte.